Determinant Analysis of International Trade and Amount of Money in Circulation Against Benchmark Rates - Rizki Rizki; Amri Darma Kurniawan S.; Rusiadi Rusiadi; Diwayana Putri Nasution; Lia Nazliana Nasution (Jurma : Jurnal Program Mahasiswa Kreatif, 2024)
The objective of this study is to investigate the impact of independent variables (currency, exports, imports, savings, and credit) on the dependent variable (BI Rate) using the Ordinary Least Squares (OLS) method. The data utilized in this research are sourced from Bank Indonesia, the Central Statistics Agency (Biro Pusat Statistik), and the World Bank, spanning the years 2010 to 2022. The focus of this research is on the macroeconomic conditions in Indonesia.The findings reveal that among the five independent variables, only the exchange rate (Kurs) exerts a partial influence on the BI Rate as the dependent variable. Moreover, collectively, the independent variables, comprising imports, exports, exchange rates, loans credit, and public savings, demonstrate a significant influence on the BI Rate as the dependent variable.